2013
DOI: 10.1159/000354602
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fractional Microneedle Radiofrequency Device in the Treatment of Primary Axillary Hyperhidrosis: A Pilot Study

Abstract: Background: Fractional microneedle radiofrequency (FMR) devices deliver energy to the deep dermis through insulated microneedles without destroying the epidermis. These FMR devices have been shown to be effective for the treatment of wrinkles, acne scars and large pores. In this study it was postulated that FMR energy could specifically affect the sweat glands, preserving the skin surface even if sweat glands were seated in the deep dermis. Objective: To evaluate the efficacy and safety of FMR for primary axil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
(34 reference statements)
0
41
0
5
Order By: Relevance
“…They demonstrated gross pathological and histological response with generation of thermally affected zones in the desired target region while providing protection to the upper skin layers. [5,10,12] Even though fractionated microneedle radiofrequency can be used as an effective, harmless, and nonaggressive method for treatment of primary axillary hyperhidrosis, further studies are needed to confirm and clearly define the histopathological changes induced in the skin by radiofrequency. [11] Our patients showed similar histologic findings of destruction of eccrine and apocrine glands and associated cell necrosis that localized at the junction of deep dermis and subcutaneous tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated gross pathological and histological response with generation of thermally affected zones in the desired target region while providing protection to the upper skin layers. [5,10,12] Even though fractionated microneedle radiofrequency can be used as an effective, harmless, and nonaggressive method for treatment of primary axillary hyperhidrosis, further studies are needed to confirm and clearly define the histopathological changes induced in the skin by radiofrequency. [11] Our patients showed similar histologic findings of destruction of eccrine and apocrine glands and associated cell necrosis that localized at the junction of deep dermis and subcutaneous tissue.…”
mentioning
confidence: 99%
“…[5] The disease evolves according to the patient's immunity. Unusual clinical manifestations have been reported.…”
mentioning
confidence: 99%
“…Studies that were found to use the HDSS tool were conducted globally, including the USA and Canada (n = 21 21,27,29,52,77,107,108,139,159,160,164,175,176,179,180,208,209,218,225,226,229 ), Spain (n = 6 167,207,210,224,230,231 ), the UK (n = 5 91,97,125,222,232 ), Germany (n = 5 2,131,145,161,227 ), Italy (n = 5 102,106, 136,214,223 ), France (n = 3 59,61,211 ), South Korea (n = 3 51,171,174 ), Australia (n = 2 53,221 ), Egypt (n = 2 213,219 ), Iran (n = 2 28,220 ), the Netherlands (n = 2 ...…”
Section: Hyperhidrosis Disease Severity Scalementioning
confidence: 99%
“…When radiofrequency (RF) encounters the skin's inherent resistance, electrical current is converted to thermal energy . MNRF's thermal effects have previously been examined histologically . However, MNRF‐induced micropores and accompanying tissue alteration have yet to be examined by noninvasive in vivo imaging techniques.…”
Section: Introductionmentioning
confidence: 99%